2022
DOI: 10.1021/acs.jpclett.2c02144
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Lubrication Effect between Oxidized Black Phosphorus and Oil Molecules Triggers Superlubricity

Abstract: Oxidized black phosphorus (BP) has been demonstrated as a promising oil-based nanoadditive because of its superior friction-reducing capability. However, the synergistic lubrication effect between oxidized BP and oil at the molecular level dominating the friction properties remains unclear. In this Letter, the synergistic lubrication effect between oxidized BP and two typical oil molecules (nonane and nonanoic acid) was explored with an atomic force microscope. The superlubricity of oxidized BP with an ultralo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…It revealed that the contact angle of the BPQD aqueous solution (37°) was smaller than that of the base liquid (53°). It is worth noting that the BPQD aqueous solution presents supereminent wettability …”
Section: Resultsmentioning
confidence: 99%
“…It revealed that the contact angle of the BPQD aqueous solution (37°) was smaller than that of the base liquid (53°). It is worth noting that the BPQD aqueous solution presents supereminent wettability …”
Section: Resultsmentioning
confidence: 99%